COMPRESSIBLE THICKNESS DEPTH DETERMINATION UNDER DIFFERENT CALCULATION METHODS OF THE SETTLEMENTS ACCORDING TO NATIONAL AND EUROPEAN STANDARDS - Lobacheva, N. G. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The comparison of the compressible thickness values and the settlements values according to the cone penetration test data in accordance with the current regulatory documents of the Belarus Republic and EUROCODE 7 «Geotechnical design» (part 1, 2) is presented. Two calculation methods of the foundation settlement for the limiting state of SLS and two methods for calculating of the settlements according to National standards are considered according to European norms. The ratios of the compressible thickness and the upset distances are determined using different calculation methods according to European and National standards. The proportions of the compressible thickness and the settlements values for different types of foundations are determined according to European and National standards.